Pengembangan Media Pembelajaran Permainan Pakpikpok Pada Kompetensi Dasar Memahami Komunikasi Kantor Untuk Meningkatkan Hasil Belajar Siswa di SMK Negeri 1 Surabaya - Eviana Permatasari; Durinda Puspasari (Universitas Negeri Surabaya, 2020)
This research aims to describe the process of developing pakpikpok game learning media on basic competency understanding office communication, analyze the feasibility of media and responses of students to the media, and analyze the effectiveness of the use the media to increase student learning outcomes at SMK Negeri 1 Surabaya. This research is a development research that refers to 4D model suggested by Thiagarajan, Semmel, and Semmel, namely define, design, develop, and disseminate. The limited trial subjects were 20 students of class X-OTKP 4 and instrument test subjects students of class X-OTKP 3. The sample of this research students of class X-OTKP 4 as the experimental class and students of class X-OTKP 5 as the control class. Data collection instrument used question and media expert validation sheets, student response questionnaire, and student learning outcomes test. Data analysis techniques include validation of question and media expert, student responses, item analysis, N-Gain analysis, completeness of student learning outcomes, homogeneity test, normality test, and hypothesis test. The results showed that the media developed included in the feasible category by obtained percentage of question experts 90,5% and media expert 96% with overall in œvery strong criteria. While the results of student responses to the media developed obtained percentage of 99% with œvery strong criteria. The results of effectiveness test showed average N-Gain the experimental class of 0,48 with œmoderate criteria, while the control class only of 0,28 with œlow criteria. Based on the results the t-test analysis of the posttest, obtained tvalue (2,586) > ttable (1,997), so that H1 accepted and H0 rejected. Can be concluded that pakpikpok game learning media developed is effective to be used as supporting learning media that can improve student learning outcomes class X-OTKP at SMK Negeri 1 Surabaya.